Adaptabilidade e estabilidade de híbridos de canola em diferentes épocas de semeadura - Lima, Luiz Henrique da Silva (2015)
The "canola" was developed by rapeseed´s breeding (Brassica napus var oleifera). Its oil is used for human consumption and production of biodiesel, and the by-product of this extraction (meal), in feed composition. The time of sowing becomes a major agent in the phenotypic characterization of plants, so, it is necessary to study its interaction with the genotype, to understand the phenotypic expression demonstrated by the plant in these specific environmental conditions. One of the alternatives is to identify cultivars with increased phenotypic stability through stability and adaptability analyzes. This work was carried out to evaluate the agronomic characteristics, the phenotypic adaptability and stability of canola hybrids, depending on sowing dates in Maringá-PR. The agronomic traits and oil yield were assessed in 2013 and 2014 growing seasons in a complete block experimental design, with the treatments arranged in split-plot, with the sowing dates in the main plots and cultivars in the subplots, arranged in 5 blocks. The interaction of the sowing dates with hybrids was studied through joint analysis of experiments in which each time of sowing in both years was considered an environment. The phenotypic adaptability and stability of the cultivars were carried out by Wricke (1962), Annicchiarico (1992) and Lin and Binns (1988) methodologies. The sowing dates exerted influence on the agronomic characteristics in the canola crop in 2013 and 2014 cropping years, but little impact on oil yield. Early hybrids (Hyola 411 and 433) showed good behavior over the tested times, especially on the Hyola 61 and 76 hybrids. The sowing dates were suitable for cultivation in the region, being indicated without restriction of time, Hyola 411 and 433 hybrids. In the methodology proposed by Wricke (1962), the genotype with the most notably phenotypic stability of grain yield and oil content was Hyola 61. However, its performance was below the average of environments. In the methodology proposed by Lin and Binns (1988) and Annicchiarico (1992), hybrids with greater phenotypic adaptability and stability in general were Hyola 411 and 433. These cultivars had the highest averages for grain yield and oil content, with predictable and responsive behavior to changes in sowing dates tested to the region of Maringá-PR.